2019
DOI: 10.1016/j.heliyon.2019.e01175
|View full text |Cite
|
Sign up to set email alerts
|

In vitro approach for evaluation of carob by-products as source bioactive ingredients with potential to attenuate metabolic syndrome (MetS)

Abstract: The potential bioactivities for alleviating Metabolic Syndrome associated risk factors were evaluated in carob (Ceratonia siliqua L.) fruit by-products, i.e. seed peel, germ and pod. Carob germ and seed peel showed higher phenolic content than pod (99.72, 80.24 and 47.06 μmol GAE g−1, respectively). Pod mostly contained gallic acid and gallotannins; seed peel and germ's showed as most abundant polyphenols quercetin and apigenin derivatives. Carob pod and seed peel revealed stronger antioxidant capacities compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…Like in AT, we also found a lower gene expression of MCP-1 and decreased macrophage infiltration in gastrocnemius explants from CSAT+ ® -supplemented mice, although the mRNA levels of pro-inflammatory cytokines were unchanged among experimental groups. However, we found a significant increase in the gene expression of the antioxidant enzymes SOD-1 and GSR which is in agreement with the antioxidant capacity shown in previous studies with carob pod extracts [31] and with extracts from other parts of carob fruit and tree [48].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Like in AT, we also found a lower gene expression of MCP-1 and decreased macrophage infiltration in gastrocnemius explants from CSAT+ ® -supplemented mice, although the mRNA levels of pro-inflammatory cytokines were unchanged among experimental groups. However, we found a significant increase in the gene expression of the antioxidant enzymes SOD-1 and GSR which is in agreement with the antioxidant capacity shown in previous studies with carob pod extracts [31] and with extracts from other parts of carob fruit and tree [48].…”
Section: Discussionsupporting
confidence: 92%
“…In visceral adipose tissue, the improved insulin resistance was associated with a decreased expression of pro-inflammatory markers such as IL-1β, TNF-α, and MCP-1 and with a decreased macrophage infiltration. Likewise, other authors have reported a direct anti-inflammatory effect of carob pod in LPS-stimulated macrophages [27,31]. Like in AT, we also found a lower gene expression of MCP-1 and decreased macrophage infiltration in gastrocnemius explants from CSAT+ ® -supplemented mice, although the mRNA levels of pro-inflammatory cytokines were unchanged among experimental groups.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Recent studies have identified many physiological effects of C. siliqua fruit and its by-products due to the existence of bioactive compounds that may be important to the promotion of human health and chronic disease prevention [68,90]. It has been demonstrated that C. siliqua is a source of bioactive ingredients with antioxidant, anti-hypertensive, and anti-inflammatory potential [91]. Our results are in line with those reported by Alzoubi et al [92], who demonstrated that the methanolic extract from C. siliqua prevented short-term memory deficit induced by chronic stress in rats, probably as a result of avoiding reduction in the brain-derived neurotrophic factor (BDNF) levels in the hippocampus.…”
Section: Effects On Anxiety-like Behavior In Ntt Test and On Spatial mentioning
confidence: 99%